Changes in ruminal fermentation and rumen bacteria population in feedlot cattle during a high lipid diet adaptation - Vesga, Daniela A. [UNESP]; Granja-Salcedo, Yury T.; Costa, Rayanne V. [UNESP]; Gomes, Kenia L.; Alves, Carvalho [UNESP]; Narvaez, Hector J.; Berchielli, Telma T. [UNESP] (De Gruyter, 2024)
This study aimed to investigate changes in feed intake and ruminal environmental parameters during a high-lipid diet transition in cattle. Eight Nellore steers were fed a control diet composed of 30% hay and 70% concentrate for 21 days, followed by the inclusion of 60 g/kg dry matter of soybean oil for 21 days. The DM intake expressed as a percentage of BW 21 days after lipid inclusion was lower (1.75% BW) than that observed during the control diet feeding (1.81% BW) (P<0.01). Steers fed the control diet had a lower pH than the ruminal pH recorded on days 7, 14, and 21 after lipid inclusion (P=0.034). Lower total short-chain fatty acid production in the rumen and lower microbial nitrogen synthesis were observed on day 7 after lipid inclusion compared to values found when steers were fed the control diet and on days 14 and 21 after lipid inclusion (P=0.041). Lipid inclusion in the diet decreased the population of protozoa on days 7, 14, and 21 (P<0.001). The abundances of R. albus and F. succinogenes were higher when steers were fed the control diet than the abundance observed on days 7, 14, and 21 after lipid inclusion in the diet (P<0.05). The first seven days of lipid diet inclusion are considered the most critical for ruminal adaptation, involving reductions in fibrolytic bacteria and changes in fermentation parameters. After 14 days the rumen showed signs of recovery and adaptation.
Keywords: fibrolytic bacteria; lipolytic bacteria; rumen protozoa; soybean oil